In memoriam - Academician Mitrofan Choban - Liubomir CHIRIAC; Dumitru Cozma (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii, 2022)
Mitrofan Cioban was born on January 5, 1942 in Copceac, Tighina county, Moldova(Romania) in the family of the farmers Mihail and Tecla Cioban. He was the fourth ofthe seven children. His parents encouraged Mitrofan to get as good an education as waspossible at the time. They sent him to a boarding school in the neighboring village ofVolontiri. Then, in 1959, he graduated from the high school of Volontiri village. Aftergraduation, he worked for a year in the local agricultural organization.